Supply Chain Risk Management: A Survey Study On Classification Of Risks - Bilişik, Murat Taha (My University, 2021)
Supply chain risk management (SCRM) is crucial for a long-term profitable, competitive and sustainable supply chain. Since defining, classifying and prioritizing risks within the scope of SCRM is an important issue in terms of both supply chain and business performance, the study has aimed to offer a road map for the companies which includes identification of the risks that companies operating in the manufacturing sector may encounter in their supply chains, calculation of risk points consisting of probability and impact values of identified risks and prioritization of risks. Using the survey method, data were collected on the probability and impact of the risks that enterprises may encounter in their supply chains. SPSS and AMOS programs were used for the validity and reliability calculations of the measurement model and as a result, risk groups have been listed by calculating probability, impact and significance scores for each risk element.
Keywords: Supply Chain Risk Management (SCRM); Risk Identification; Prioritization Of Risks